Standardization of the human proximal tubule cells and cell culture media for the bioartificial kidney - Teo, Pei Yun. (2010)
The Institute of Bioengineering and Nanotechnology (IBN) has embarked on research work toward the building of the bioartificial kidney (BAK), which consists of living primary human renal proximal tubule cells (HPTCs) grown as confluent monolayers in a bioreactor. These HPTCs would provide for the immunomodulatory, active transport and endocrinologic functions of an actual kidney which are lacking in the hemodialysis machine, currently used for treatment. However, there is a need for a standardized immortalized HPTC cell source and for the cells to be maintained as a well-differentiated and functional epithelial monolayer. Presently, research has been carried out using primary cells which are harvested from different donors, thus having a batch-to-batch variability. Motile myofibroblasts, which are usually associated with HPTC monolayer disruption and loss of epithelial cell proteins, are also present in the HPTC cell culture. Although the origins of the myofibroblasts are undefined, increasing evidence has pointed to HPTCs which may have undergone the process of epithelial-to-mesenchymal transition (EMT) to form myofibroblasts. To address the problems, we tried to create immortalized HPTCs (hT1-4) which would be able to provide for a standardized cell source. We expressed human telomerase reverse transcriptase (hTERT) in HPTCs and sorted the cells into single cell cultures, with the flow cytometer. We managed to generate 8 homogeneous clones. The hT1-4 clones were not immortalized but had an extended life-span and were positive for epithelial cell proteins such as zonula occludens (ZO-1) with a low percentage of myofibroblasts. However, they lacked ii the functional - glutamyl transpeptidase (GGT) activity and thus could not be used as a replacement for the HPTCs.